Relações entre a Educação Musical Especial e o desenvolvimento da comunicação social em crianças autistas - Gleisson do Carmo Oliveira (2020)
Autism, according to the fifth edition of the American Psychiatric Association's Diagnostic and Statistical Manual for Mental Health (DSM-5), is characterized as a neurodevelopmental disorder that affects social communication skills and behavior from early childhood. There are several aspects related to communication in which autistic people may experience difficulties, such as communicative intent, eye contact, joint attention, shift changes, imitation, symbolism and narrative. Recent studies have shown that autistic people, in general, can be highly responsive to music, as well as improve their communication through musical interventions. Special Musical Education deals with the teaching of music to people with disabilities. It was the intervention modality used by this research, whose objective was to study the relationship between Special Musical Education and the development of the social communication of autistic children. In this sense, this research asked: what relations could be established between Special Musical Education and the development of autistic child’s social communication? Thus, a mixed method study was carried out, through the combined use of quantitative and qualitative methods. Initially, fifteen autistic children were selected and randomly allocated to two groups. Each Group participated in two formats: Group 1 (Experimental / Follow up) and Group 2 (Control / Experimental). In the experimental participations, both Groups were submitted to a semester of music lessons. In the Follow up / Control participations, the Groups were absent from the musical intervention. Three scales (ABFW-Pragmatic Test, DEMUCA Scale and IMTAP) were used to assess children's musical and socio-communicative development, at each stage of the research, in their respective groups.The numerical data were analyzed statistically, and the Cronbach's Alpha Test was first performed, by which the internal consistency of the three scales was confirmed: Pragmatic Test of the ABFW Scale (a = 0.82); DEMUCA scale (a = 0.98) and IMTAP (a = 0.98). Next, intergroup and intragroup analyzes were performed using the GEE (Generalized Estimating Equations) method, a way to account for the correlation between the repeated measures of the same individuals. By the intergroup analysis, the Groups were considered homogeneous at the beginning of the research, with differentiation after the intervention period of Group 1 (a first indication of the influence of musical activity on the development presented by the children). Then, by the intragroup analyzes, it was found that the two Groups had significant development in 10 categories of the three scales (Shared game, Restrictive behaviors, Social-Cognition interaction, Perceptionsound exploration, Vocal exploration, Follows instructions, Musical changes, SingingVocalizing, Rhythm, Fundamentals of Expressive Communication) based on their participation in music classes, thus demonstrating an improvement in children’s social communication and musical development. The qualitative results, obtained through a Focus Group carried out with the children's parents, pointed out that both Groups had an improvement in restrictive behaviors, social interaction, communication, in addition to developing musical skills. Reflections from the intersection between quantitative and qualitative data demonstrated that Special Musical Education, in fact, favors social communication and that musical activity, mediated live by the educador, instigates autistic's innate musicality, opening communication windows without the need for words. The autistic’s Communicative Musicality, in a latent state, but mobilized and enhanced by musical activity, constitutes an opportunity that, if well explored, allows the breaking of barriers to communication and the integration of subjectivities. It was also evident that the solidary engagement provided by the musical activity at different levels (educator / child, parents / child, educator / parents) was an element of great importance for the results presented by the research children. Also, the different strategies used by Special Music Education contributed to the social communication improvement of the participating children. It is important to emphasize that a generalization of this reasearch results deserves care, given the small number of participants involved (n = 15). However, evidence for the existence of an interface between musical development and the development of social communication were pointed here. Further studies are needed to cover a larger population, as well as a longer intervention period.